ADVANCED APPROACH FOR HYPER ACTIVITY CHILDREN TREATMENT USING EEG AND EMG BIOFEEDBACK SYSTEM - KRIPA, N.; VASUKI, R.; KANNA, R. KISHORE (International Journal of Psychosocial Rehabilitation, 2020)
In the paper, an EEG and EMG biofeedback framework for treating hyperactive kids who endure consideration shortage and learning inabilities is described. The framework can work in an independent mode or with an IBM PC. In the main case, the sign which differs with the patient's brain and muscle movement level are feedbacked to the patient on the web. It tends to be utilized for clinical applications. In the second case, the EEG-EMG input signals are collected by IBM PC, and at that point, handled with sophisticated digital sign preparing methods. The later mode gives a productive and adaptable route for the examination and input of EEG and EMG signals[1].